The PROSES PENGEROLAN BATANG RUMPUT PAYUNG UNTUK MENGHASILKAN SERAT MELALUI METODE REDUKSI MENGGUNAKAN GEARBOX - Danang Murdiyanto; Bernardus Crisanto P.B; Yosep Ardi Ang S (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2021)
The design of production machines always requires an innovation with the aim of making improvements and to improve production results. The umbrella grass stem pressing roller machine in previous research can still be developed to improve the performance of the engine. In this research, the first method used is to design a transmission system and gearbox reduction with the main drive motor with 1 HP power specifications and 1400 rpm rotation. The second method is to test the press roller machine. In this study, 3 variations of loading were made (35kg, 40kg, and 45kg) and for each loading variation 3 fiber samples were taken for the tensile test. The results obtained from this research are that the transmission system is selected by using a wormgear type gearbox with a rotation ratio (i) of 1/20 and from the calculation, the rotation of the press roller is obtained by 20 rpm. The results of the fiber tensile test, obtained the highest tensile strength value at the loading variation of 35 kg with the resulting fiber is better. Whereas for the average tensile stress of the 3 samples the result is 61.136 MPa.